Pengaruh Bentuk Penghalang Bervariasi Pada Proses Perpindahan Panas - Beni Anwarudin; Gatut Rubiono; Adi Pratama Putra (Virtual of Mechanical Engineering Article, 2022)
Handling heat energy in the industrial world is very necessary. Heat exchangers have a fluid system that can be designed and developed using pipes. Heat transfer in a heat exchanger is a support for the performance of a heat exchanger to make it better. In this study, a heat exchanger was tested by placing a variety of barriers on the field of heat transfer flow and the addition of variations in the flow rate on the heat pipe. This test uses a aliran inch water flow pipe and a 2.5 inch iron tube pipe and a barrier material using aluminum. Based on the test results obtained a graph of varying heat transfer increases in each barrier. Differences in barrier variations and variations in water discharge greatly affect the value of heat transfer results. The purpose of this study was to look for the effectiveness and effect of adding a flow barrier to the performance of heat transfer in a heat exchanger. Keywords: Heat Exchanger, Effectiveness of Heat Transfer Heat